(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: Breast involvement by immunolymphoproliferative disorders is rare. Primary & secondary malignant lymphomas of the breast are much more common than multiple myeloma, of which only 18 cases were reported in previous literature, till the year 2000. Case presentation: We report a young female patient presented simultaneously with bilateral multiple breast masses & pathological fracture in right humorous that proved later on via histopathological examination to be a case of multiple myeloma associated with extramedullary plasmocytoma involving breasts. Discussion and Conclusion: There were diagnostic difficulties caused by the lack of specific radiological & sonographic features that differentiate between primary or secondary breast tumor & breast infiltration by immunolymphoproliferative disorders. Key words: Plasma cell diseases, plasmocytoma, multiple myeloma, breast mass